Three Seventh-Century B. C. E. Hoards of Silver Jewelry from Tel Miqne-Ekron - Golani, Amir (Bulletin of ASOR, 1998)
Three silver jewelry hoards dated to the seventh century B. C. E. were found at Tel Miqne-Ekron during the 1985, 1988, and 1992 excavation seasons. These hoards are important for three reasons. First, no other local late Iron Age jewelry collection is as securely dated as the Ekron hoards, which make them a basis for evaluating other, less securely dated jewelry finds from the first millennium B. C. E. Second, the contents of the hoards and the context in which they were found can help to define their function. The 1985 and 1988 hoards are composed primarily of broken or damaged silver jewelry along with cut silver (Hacksilber) pieces, while the 1992 cache contains mostly intact jewelry items. A study of the composition and character of these collections suggests that the 1985 and 1988 hoards were probably currency hoards, while the 1992 cache may have been a jeweler's inventory or a private hoard of valuable objects. Finally, such a large and securely dated collection of silver jewelry is of great importance for understanding the late Iron Age jeweler's craft and the cultural influences prevalent at Tel Miqne-Ekron during the seventh century B. C. E. The style of the silverwork shows strong Phoenician influence, while a few pieces also exhibit Neo-Assyrian characteristics.